PENGARUH LATIHAN JUMP SHOT DIDAHULUI DRIBBLE TERHADAP HASIL JUMP SHOT PADA PERMAINAN BOLA BASKET TIM PUTRA SMA NEGERI 2 PEKANBARU - Nadya Khairunisa; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem of this research is the lack of athletes in the jump shot technique, it can be seen when athletes during training or competing in doing jump shots that there are still many inaccurate shots that do not produce points. In addition, researchers observed that players still lacked dribbling skills when they wanted to do jump shots. This greatly affects the athlete's opportunity to make accurate jump shots and this is also very detrimental to the team in obtaining points. For this reason, researchers consider it necessary to do research on the effect of jump shot exercises preceded by dribbling on the jump shot results in the basketball game for the men's team at SMA Negeri 2 Pekanbaru. The design of this research is pretest posttest one group design. The population in this study was the men's basketball team of SMA Negeri 2 Pekanbaru, totaling 12 people. The sampling technique used is total sampling, where the entire population of 12 people is made into the sample. By using the research test instrument, namely the shooting test norm for 30 seconds. After that, the data was processed statistically, to test for normality using the Lilliefors test at a significant level of 0.05α. The hypothesis proposed is that there is an effect of jump shot training preceded by dribble on the jump shot results in the basketball game for the men's team at SMA Negeri 2 Pekanbaru. Based on the analysis of the normality test of the data, the results of the pree-test resulted in Lcount of 0.1649 and Ltable of 0.242 meaning Lcount < Ltable. while the post-test data resulted in Lcount of 0.1831 and Ltable of 0.242, meaning that Lcount < LTable, then the data was normally distributed. Based on statistical data analysis, there is an average pre-test of 3.916 and an average post-test of 7.583. Then based on the analysis of the t-test, the t-test value is 10.90 and the t-table is 1.796, so tcount > ttable, then Ho is rejected and Ha is accepted. Thus, it can be concluded that there is an effect of jump shot training preceded by dribble on the jump shot results in the basketball game for the men's team at SMA Negeri 2 Pekanbaru. Key Words: Jump Shot Preceded By Dribble, Jump Shot Result